MOTIVASI JERMAN DALAM MENERIMA PENGUNGSI ASAL SURIAH PADA TAHUN 2015 - Mila Fitri Yeni (Frequency of International Relations (FETRIAN), 2019)
This research aims to analyze Germany’s Motivation to accept Syrian refugee in 2015 at German policy of Open Door Policy. A foreign policy that was chosen by the state is rational choice by calculating the benefit earned and cost paid through the policy based on national interests. This research was analysed using the concept Rational Model of Decision Making by Karen A.Mingst this concept sees the formulation of a state’s foreign policy based on the considerations of the costs and benefits a state gets on the issue at hand, in which the state will choose a policy with greater profits than its sacrifices. The researcher concluded that Germany’s open door policy toward Syrian refugees was a rational choice because it has that advantage in the form of adding labor that has an effect on the economic aspect for Germany